2017
DOI: 10.1080/02652048.2017.1413147
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of β-cyclodextrin inclusion complexes with natural antimicrobial agents: thymol, carvacrol and linalool

Abstract: Beta-cyclodextrin (β-CD) inclusion complexes with naturally derived antimicrobial (AM) agents: thymol, carvacrol and linalool were prepared using a co-precipitation technique. Conditions including solvent composition, temperature, reaction time and total solvent volume were investigated to optimise the inclusion efficiency (IE) and yield. Electrospray ionisation mass spectrometry was used to confirm the formation of the thymol/β-CD complex and gas chromatography was used to quantify the amount AM agent that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 53 publications
(71 reference statements)
0
20
0
Order By: Relevance
“…Scientists all over the world have thoroughly examined and characterized the entrapment of pure natural compounds (e.g., polyphenols [ 19 , 20 ], flavonoids [ 21 , 22 ], alkaloids [ 23 , 24 , 25 ], terpenoids [ 26 ]), EOs [ 27 , 28 ] (e.g., tee tree oil [ 29 ], oregano [ 30 ], Eucalyptus staigeriana [ 31 ]) and extracts (e.g., propolis [ 32 , 33 ], olive leaves [ 34 ], Chimonanthus praecox extract [ 35 ]) in α-, β- or γ-CDs or modified CDs for several applications, revealing significantly improved properties to the final complexes [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scientists all over the world have thoroughly examined and characterized the entrapment of pure natural compounds (e.g., polyphenols [ 19 , 20 ], flavonoids [ 21 , 22 ], alkaloids [ 23 , 24 , 25 ], terpenoids [ 26 ]), EOs [ 27 , 28 ] (e.g., tee tree oil [ 29 ], oregano [ 30 ], Eucalyptus staigeriana [ 31 ]) and extracts (e.g., propolis [ 32 , 33 ], olive leaves [ 34 ], Chimonanthus praecox extract [ 35 ]) in α-, β- or γ-CDs or modified CDs for several applications, revealing significantly improved properties to the final complexes [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ICs of FO:β-CD was produced by coprecipitation method based on the previous research with some modifications [15], [16]. This study carried out some volume variations of FO and β-CD, as shown in Table I.…”
Section: Resultsmentioning
confidence: 99%
“…Guest molecules must have the appropriate size or shape to enter the cavity in the host molecule. Stereochemistry and polarity of host and guest molecules determine the effectiveness of encapsulation [16]. In aqueous solution, β-CD can form complexes with several guest compounds (guest) by inserting guest molecules into the middle cavity of the β-CD molecule.…”
Section: A Mechanism Of the Ics Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…The CO technique utilized manual mixing of the components followed by progressive addition of distilled water (400 µL) forming a solution, while for preparing the inclusion complex by KN method, β-CD and ICaf were kneaded and dispersed in 8 mL of water using magnetic stirring (Kasvi, K40-1810, Kasvi São Paulo, Brazil) for 36 h to obtain a paste. All samples were stored in hermetically sealed containers [ 37 ].…”
Section: Methodsmentioning
confidence: 99%